2006
DOI: 10.1598/jaal.50.4.5
|View full text |Cite
|
Sign up to set email alerts
|

“The Teacher Said My Story Was Excellent”: Preservice Teachers Reflect on the Role of the “External” in Writing

Abstract: When asked to reflect on their experiences with writing, preservice teachers attributed their successes and failures to a number of factors. Some of these attributions, such as those made to effort and ability, were internal in nature. However, the most frequently occurring references were to an external factor: influential others. Preservice teachers discussed the role parents, siblings, and, most often, teachers played in their development as writers. These findings call into question the notion that writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 39 of the 82 studies we reviewed, PTs’ beliefs or attitudes about writing emerged as an important factor. These studies showed that PTs often approach writing with negative attitudes that may be attributed to receiving harsh criticism as EC-12 students (e.g., Hall & Grisham-Brown, 2011; Norman & Spencer, 2005), a lack of ownership in their writing experiences (e.g., Morgan, 2010), not feeling like they had supportive writing instruction or feedback (e.g., Gallavan, Bowles, & Young, 2007), or not believing they have natural ability as a writer (e.g., Mathers, Benson, & Newton, 2006; Street, 2003). Furthermore, few PTs indicated writing for pleasure or writing in extended ways beyond academic purposes (e.g., Gardner, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In 39 of the 82 studies we reviewed, PTs’ beliefs or attitudes about writing emerged as an important factor. These studies showed that PTs often approach writing with negative attitudes that may be attributed to receiving harsh criticism as EC-12 students (e.g., Hall & Grisham-Brown, 2011; Norman & Spencer, 2005), a lack of ownership in their writing experiences (e.g., Morgan, 2010), not feeling like they had supportive writing instruction or feedback (e.g., Gallavan, Bowles, & Young, 2007), or not believing they have natural ability as a writer (e.g., Mathers, Benson, & Newton, 2006; Street, 2003). Furthermore, few PTs indicated writing for pleasure or writing in extended ways beyond academic purposes (e.g., Gardner, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Internationally in pre-service and in-service contexts, teachers' development as writers is often nurtured and they are encouraged to adopt the position of teacher and writer in school. Significantly, research indicates that teachers' conceptions of literacy, literate identities and pedagogic practice, frame, shape and often limit students' identities, both as writers (Bourne 2002;Mathers, Benson and Newton, 2006;Ryan and Barton 2014) and as readers (Hall et al 2010;Hall 2012). Yet relatively little appears to be known about teachers' attitudes to writing, their sense of themselves as writers and the potential impact of teacher writing on pedagogy or student outcomes in writing.…”
Section: Introductionmentioning
confidence: 99%
“…English language arts (ELA) teacher candidates enter teacher education with diverse writing experiences that influence their perceptions of writing instruction (Draper, Barksdale‐Ladd, & Radencich, ; Mathers, Benson, & Newton, ). Like K–12 students, teacher candidates’ experiences with writing are not limited to teacher‐led, school‐sanctioned writing tasks.…”
mentioning
confidence: 99%